Direct Access to MIDA Acylboronates through Mild Oxidation of MIDA Vinylboronates. (24th October 2017) - Lepage, Mathieu L.; Lai, Samson; Peressin, Nicolas; Hadjerci, Romain; Patrick, Brian O.; Perrin, David M.
Abstract: Acylboronate esters/trifluoroborates represent an elusive class of boronates that are of increasing interest for both fundamental study as well as applications at the interface of chemistry and biology. Their preparation has been limited by the use of strongly basic anions, often introduced in multistep reactions. Herein, we demonstrate the facile preparation of acylboronate N‐methyliminodiacetyl (MIDA) esters from alkenyl‐2‐boronate esters through mild dihydroxylation and meta ‐periodate cleavage. Given the well‐known functional‐group tolerance of this mild reaction sequence and the availability of alkenyl‐2‐boronates, this method should greatly increase access to acylboronate MIDA esters.